Kajian Penggunaan Paclobutrazol terhadap Pertumbuhan Semai Agathis Loranthifolia (The Study of paclobutrazol on the growth of Agathis loranthifolia seedlings) - Ombo Satjapradja; L Setyaningsih; Dida Syamsuwida; Ateng Rahmat (Jurnal Manajemen Hutan Tropika, 2006)
Paclobutrazol is one of hormone which able to inhibit the growth of tree seedling. This kind of hormone is usually used extensively in horticulture in stimulating flowering and enhancing fruiting. The objective of the research was to know the effect of paclobutrazol on the growth of Agathis loranthifolia seedlings during storage under different condition, in order to support seedling supply programs for forest establishment and rehabilitation. There were two factors of the trial i.e.) growth inhibitors (paclobutrazol, NaCl and aquadest) and 2) storage conditions (growth house, heavy shading and light shading). A complete randomized design with two factors and 3replication were used in this trial. The result of the research showed that the treatment of paclobutrazol to the seedlings stored at a green house gave an effect to the height and diameter growth of Agathis loranthifolia seedlings which were lower than those treated by NaCl and aquades. While paclobutrazol treated seedlings stored under light shading, gave higher value of seedling height and diameter than those stored under green house condition and heavy shading. The highest value of seedling survival Agathis loranthifolia achieved by paclobutrazol treated seedlings which were stored at the green house and under light shading. Field testing after 3 months plantation showed that paclobutrazol – treated seedlings and seedlings, stored under light shading gave a highest value of seedling survival (100%) and seedling quality index (0,095).Keywords : paclobutarazol hormone, seedling storage technique, recalcitrant seed, seedling survival,  seedling quality index.